Learning Analysis of the Long Jump Material Using the Playing Method for Junior High School Students - Rubi Yatno; Rahmat Putra Perdana; Edi Purnomo; Eka Supriatna; Putra Sastaman (UNIVERSITAS SERAMBI MEKKAH, 2022)
This study aims to determine how the learning outcomes of the squat style long jump using the play method in class VIII students of State Junior High School 1 Kuburaya. The form of research used in this research is experimental research with two stages consisting of planning, implementation, observation, reflection, and conclusion. The subjects in this study were Class VIII students, totaling 35 students. The results of improving soccer passing learning using the inside of the foot are obtained by comparing the observation value with the initial test before the action known as